THE STATE COUNCIL OF EDUCATION OF SAO PAULO AND THE OFFENSIVE TO UNIVERSITY AUTONOMY - Lopes de Sena, Marcos Danillo; Paula Resende, Fernanda Motta de [UNESP] (Fundacao Univ Tocantins, 2019)
Deliberation no = 111/2012 unilaterally determined the reformulations for undergraduate courses. This unilateral imposition allows us to reflect and dialogue about the role of the State Council of Sao Paulo's Education. In this sense, this research aims to investigate the determinations of the State Council of Sao Paulo's Education and its implications in the Universities of Sao Paulo State. With this investigation,we intend to problematize about the performance and the functioning of the CEE/SP and its attributions to the state educational system. As instruments of data collection, a documentary and bibliographic research was carried out.
Keywords: Higher Education; University Autonomy; State of Sao Paulo; State Council of Education